Activation of cannabinoid 2 receptors by JWH-133 protects against ovarian ischemia-reperfusion injury in rats. (4th July 2021) - Onat, Taylan; Demir Caltekin, Melike; Doğanyigit, Züleyha; Turkler, Can; Kaymak, Emin; Kara, Mustafa; Serdar Yalvac, Ethem
ABSTRACT: We investigated the efficacy of activated cannabinoid 2 receptors for alleviating ovarian ischemia-reperfusion injury in rats. Female Wistar albino rats were divided randomly into six groups: ischemia-reperfusion (IRG); ischemia-reperfusion + 0.2 mg/kg JWH-133 (JIRG1), ischemia-reperfusion + 1 mg/kg JWH-133 (JIRG2); ischemia-reperfusion + 5 mg/kg JWH-133 (JIRG3); solvent control, and sham control. Ovarian ischemia was established for 3 h followed by reperfusion for 3 h. Ovarian tissue was investigated using histology, immunohistochemistry and biochemistry. Administration of JWH-133 synthetic cannabinoid reduced nuclear factor kappa-B immunoreactivity as well as TUNEL positivity scores and malondialdehyde levels. These reductions were significant in all cases except for the malondialdehyde levels in the 1 mg/kg JWH-133 group. Activation of cannabinoid 2 receptors by JWH-133 reduced ovarian ischemia-reperfusion injury due to its antioxidant and anti-inflammatory effects.